Legitimising Lockdown in Saudi Arabia: A Political Discourse Analysis of Platformed Government Communication During a Public Health Emergency - Jaber Salman Ali Alraythi; Tariq Elyas; Nazim Alqahtani; Rasha Gazzaz (Language, Technology, and Social Media, 2026)
This study applies Teun A. van Dijk’s Political Discourse Analysis (PDA) framework within Critical Discourse Analysis (CDA) to examine Saudi political communication during the COVID-19 crisis. It analyses three key texts: King Salman’s national address, the Ministry of Health’s (MoH) public awareness campaigns particularly the “Educational Text Messages” and the MoH spokesman’s speech on vaccines. The study explores how language was strategically used to legitimise government actions, construct a shared sense of national responsibility, and promote compliance with health measures. Through macro-level thematic, micro-linguistic, and socio-cognitive analysis, the research reveals that Saudi discourse employed religious authority, national identity, emotional appeals, and inclusive language to reinforce trust and unity among citizens and expatriates. The findings show a hierarchical, top-down communicative structure integrating religious legitimacy, technocratic guidance, and scientific reassurance to influence public perception and maintain ideological cohesion. Additionally, the strategic use of multiple genres and multilingual media ensured message consistency and broad reach across society. Overall, the study highlights how political discourse functions as both an ideological and communicative instrument in crisis governance, enriching the understanding of how language mediates power, ideology, and social mobilisation in centralised political contexts.